SAPS members' experience of diversity and diversity training within the SAPS - Everton, Wilma (Rhodes University, Faculty of Humanities, Department of Psychology, 1999)
During this study, an attempt was made to explore the opinions and attitudes of members of the South African Police Service (SAPS) towards issues of diversity before, immediately after and three months after participating in diversity training workshops presented by the SAPS Training Division during 1997 in Port Elizabeth. The aim of this thesis was not to assess the diversity training itself, but to discover if the training, as currently presented, in any way influenced the attitudes of participants. In order to meet this goal, literature and empirical studies were conducted. The literature study sets the theoretical foundation pertaining to the history of the SAPS and the attitudes and prejudices of and diversity among SAPS members. During the empirical research phase, a non-probability purposive sampling procedure was adopted. Four of a range of diversity workshops presented by the Training Division of the SAPS during 1997 were selected for the purpose of this study. An internal SAPS process was used to nominate members to attend the workshops. The researcher requested the participants in each of the four workshops to complete a self-administered questionnaire before as well as after the workshop concerned. Immediately after each of the four workshops, a short interview was held with each attendee. To explore the stability of any change evident from responses on the questionnaires completed after the workshops, the attendees were again requested to complete the same questionnaire three months later. To increase the validity of any conclusion that attitudinal change was related to the workshop, a control group was used. This study has revealed that a cross-spectrum of SAPS members of both sexes and diverse racial backgrounds believe that various forms of discrimination exist within the SAPS. It confirmed that the diversity training presented by the SAPS Training Division is a useful instrument to heighten members' awareness of the different norms and customs of other cultural/ethnic groups and of the necessity that the SAPS should be constituted of a cross-spectrum of racial groups reflecting the South African society. Finally, based on the research findings, recommendations were made involving management and its supportive services and diversity training.
Keywords: Police -- South Africa -- Attitudes; Cross-cultural orientation; Sex discrimination in criminal justice administration -- South Africa; Discrimination in criminal justice administration -- South Africa